The Influence of Work Culture and Work Discipline on Patient Safety at Bogor Islamic Hospital - Sukaisih Susanti; Eddy Hermawan Hasudungan; Irawan R D Budianto (IJBLE Scientific Publications Community Inc., 2026)
Hospitals bear a strategic responsibility for ensuring patient safety throughout the continuum of care. Patient safety is not only a key indicator of healthcare quality but also reflects the professionalism of healthcare personnel and the effectiveness of hospital management systems. This study aimed to examine the influence of work culture and work discipline, individually and in combination, on patient safety at Bogor Islamic Hospital. A quantitative, cross-sectional design was employed. Total sampling was used, involving 50 nurses as respondents. Data were collected through structured questionnaires and analysed using multiple linear regression. The findings indicate that work culture has a statistically significant positive effect on patient safety (t = 4.096, p < .001). Work discipline also has a positive and statistically significant effect on patient safety (t = 4.771, p < .001). Simultaneously, work culture and work discipline significantly influence patient safety (F = 15.648, p < .001), with a coefficient of determination (R² = .400), indicating that 40.0% of the variance in patient safety is explained by these two variables. These findings suggest that both organisational and behavioural factors play meaningful roles in shaping patient safety in hospital settings.